If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(3 + -1x) = -4x + -6 (3 * 10 + -1x * 10) = -4x + -6 (30 + -10x) = -4x + -6 Reorder the terms: 30 + -10x = -6 + -4x Solving 30 + -10x = -6 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 30 + -10x + 4x = -6 + -4x + 4x Combine like terms: -10x + 4x = -6x 30 + -6x = -6 + -4x + 4x Combine like terms: -4x + 4x = 0 30 + -6x = -6 + 0 30 + -6x = -6 Add '-30' to each side of the equation. 30 + -30 + -6x = -6 + -30 Combine like terms: 30 + -30 = 0 0 + -6x = -6 + -30 -6x = -6 + -30 Combine like terms: -6 + -30 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| 2a+8=54 | | -12=-5-6x+11 | | D+-8d+7=0 | | 2x+12+6x-10=180 | | -0.06y+0.08(1100-y)=0.36y | | 8x+12=9x+5 | | -5a-5(1-4a)=-5+4a | | 2(4+x)=4x+3 | | 5x-16=4x+7 | | 4x+3x=6x-6 | | 57=3y | | 3y+1=28 | | 5x-20=2x+4 | | 5d-2=63 | | -0.06y+0.08(1100-y)=0.36 | | 4x+3x=6x | | -3x+9=2x-6 | | 9n-12=69 | | 3y+14=5 | | -6x-17=-4x+7 | | 8(x+2)=3x+5 | | -11*3=15+-6*3 | | 7.8p-18=2.6p-5 | | 3x+8x-40=48 | | 9(x-5)=8(x-1) | | -96+5x=-8x+86 | | 2x+2=x+56 | | -3n-4=-2-3n | | 12x+14y=112 | | D-8d+7= | | 5x+2-x=2(x+3) | | 5(3x+2)-4+2(-5x+4)-3+14+2(5x-1)-7(3x+2y)+5(4x+2y)+11(5x+3y)+4(12x+5y)= |